Allicin-Based Transethosomal Gel: A Novel Herbal Approach for Psoriasis Treatment - Yogita K. Kothawade; Deepak Sonawane; Yogesh Sharma (Asian Journal of Pharmaceutical Research and Development, 2025)
Allicin, Garlic is the source of allicin, a bioactive organosulfur molecule that has shown strong antibacterial, anti-inflammatory, and immunomodulatory properties, making it a possible topical treatment for psoriasis. However, because of its limited skin penetration and poor aqueous stability, its therapeutic value is limited. Highly flexible lipid vesicles called transethosomes, which are made of phospholipids, ethanol, and edge activators like sodium cholate, have become sophisticated nanocarrier systems that can improve the transport of drugs through the skin.In this review, the development and usage of transethosomal gels loaded with allicin as a new psoriasis treatment strategy is discussed. The article discusses important formulation parameters, physicochemical characteristics, preparation methods, and advantages over traditional delivery methods. Transethosomal systems have been shown to improve drug entrapment, extend release profiles, increase skin permeability, and improve therapeutic effects throughout the body of current literature. These characteristics highlight how transethosomal gels laden with allicin may help develop herbal-based topical treatments for inflammatory skin conditions like psoriasis.